Computer Technologies and Teaching Aids for Distance Learning in Educational Institutions Under Quarantine - et. al., Tatyana Pakhomova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The global spread of coronavirus infection has paralysed the work of many areas of economic, business, and, of course, educational activities of almost all countries on the planet. Unfortunately, Ukraine is no exception and a quarantine regime has been introduced in this country. The way out of the current situation in education in Ukraine was the introduction of distance learning in all educational institutions, which created new challenges for both teachers and students. The purpose of the paper was to study information technologies, tools and methods of learning that can be used for distance learning in educational institutions under quarantine. As a result, authors analysed world practices in ensuring the educational process within the framework of distance learning. The advantages and disadvantages of distance learning technologies for both higher education institutions and higher education seekers were identified. The research algorithm was presented in the form of systemic interrelations between the form of distance learning and information and software resources. The main features of such remote technologies as Moodle, Google Classroom, and video communication systems Zoom and Hangouts Meet were analysed.